TEACHING AND ORGANIZATION OF PRESCHOOL EDUCATION SYSTEM - Abduramanova Diana Valeryevna, Abduramanova Diana Valeryevna (Журнал иностранных языков и лингвистики, 2021)
Preschool education is an integral part and the first link in a unified system of continuous education, where the foundations of the personality are being formed. In accordance with the generally accepted age periodization of human development, preschool childhood covers the period from birth to 6 years old, when the child’s motor, sensory and intellectual spheres are actively formed, his speech and basic mental processes, abilities and socially significant qualities develop.